THE ROLE OF LOCUS OF CONTROL IN REACTIONS TO BEING PROMOTED AND TO BEING PASSED OVER: A QUASI EXPERIMENT. - Lam, S. S. K.; Schaubroeck, J. (Academy of Management Journal, 2000)
The attitudinal and behavioral effects of being promoted and being rejected for promotion were examined in a quasi experiment conducted at an international bank in Hong Kong. Promoted tellers who had more internal locuses of control (LOC) maintained improved attitudes across 3- and 18-month posttest intervals. Attitudes returned to baseline levels by the second posttest among external-LOC individuals who had been promoted. There was no change in attitudes among people passed over for promotion. Absenteeism and job performance both decreased among promotees. The implications for the administration of promotions are considered.